Diverse Environmental Microbiota as a Tool to Augment Biodiversity in Urban Landscaping Materials - Hui, Nan; Grönroos, Mira; Roslund, Marja I.; Parajuli, Anirudra; Vari, Heli K.; Soininen, Laura; Laitinen, Olli H.; Sinkkonen, Aki; , The ADELE Research Group (Frontiers in Microbiology, 2019)
Human activities typically lead to simplified urban diversity, which in turn reduces microbial exposure and increases the risk to urban dwellers from non-communicable diseases. To overcome this, we developed a microbial inoculant from forest and agricultural materials that resembles microbiota in organic soils. Three different sand materials (sieved, safety and sandbox) commonly used in playgrounds and other public spaces were enriched with 5 % of the inoculant. Skin microbiota on fingers (identified from bacterial 16S rDNA determined using Illumina MiSeq sequencing) was compared after touching non-enriched and microbial inoculant-enriched sands. Exposure to the non-enriched materials changed the skin bacterial community composition in distinct ways. When the inoculant was added to the materials, the overall shift in community composition was larger and the differences between different sand materials almost disappeared. Inoculant-enriched sand materials increased bacterial diversity and richness but did not affect evenness at the OTU level on skin. The Firmicutes/Bacteroidetes ratio was higher after touching inoculant-enriched compared to non-enriched sand materials. The relative abundance of opportunistic pathogens on skin was 40–50 % before touching sand materials, but dropped to 14 % and 4 % after touching standard and inoculant-enriched sand materials, respectively. When individual genera were analyzed, Pseudomonas sp. and Sphingomonas sp. were more abundant after touching standard, non-enriched sand materials, while only the relative abundance of Chryseobacterium sp. increased after touching the inoculant-enriched materials. As Chryseobacterium is harmless for healthy persons, and as standard landscaping materials and normal skin contain genera that include severe pathogens , the inoculant-enriched materials can be considered safe. Microbial inoculants could be specifically created to increase the proportion of non-pathogenic bacterial taxa and minimize the transfer of pathogenic taxa. We recommend further study into the usability of inoculant-enriched materials and their effects on the bacterial community composition of human skin and on the immune response.